Migrants and global value chains: Evidence from Dutch firms - Aksel Erbahar; Omer Tarik Gencosmanoglu (Tinbergen Institute, 2021)
This paper examines the relationship between migrant workers and global value chain linkages using a rich employer-employee dataset from the Netherlands for 2010-2017. We merge the employer-employee dataset with international trade data and extract firms' country-product specific imports. We use OLS and PPML regressions at the firm-country-year level with high dimensional fixed effects, and find that firms that employ migrants from a specific country are more likely to import inputs from and establish supply chain linkages with that country. Our benchmark specification indicates that a 10% increase in the number of migrant workers raises their employer's probability of sourcing inputs from their origin country by 0.2 percentage points, explaining about a fifth of the average probability of importing inputs from a given country. Results at the intensive margin are qualitatively similar but smaller in magnitude. Digging deeper, we find that the effect is driven by first generation immigrants, and that the second generation immigrants have a marginal impact on their employers' sourcing decisions. Our results indicate that migrants help erode informational barriers and help their employers to integrate into global value chains.
Keywords: F14; F16; 330; immigration; global value chains; employer-employee